(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
This article examines the impact of different application times and rates of biostimulants on the growth and development of Crotalaria juncea. The study was conducted in field conditions in Jizzakh region, assessing the plant height, number of leaves, branches, flowers, and pods throughout various phenological stages. The biostimulants “UzGumi” and “Geogumat” were applied at sowing and during specific vegetative phases, resulting in significantly improved growth parameters. “Geogumat” showed the most notable effects. The findings suggest that proper and timely use of biostimulants plays a crucial role in optimizing Crotalaria growth and yield potential.